3 Identification of anti-apoptotic caspase 9b in head and neck squamous cell carcinoma. Issue 5 (May 2015) - ,; Pries, R.; Wollenberg, B.
Abstract : Introduction: Paclitaxel is an effective chemotherapeutic agent against various human tumors inducing apoptosis via binding to β tubulin of microtubules and arresting cells mainly in the G2/M phase of the cell cycle. However, the underlying specific molecular mechanisms of Paclitaxel on HNSCC (head and neck squamous cell carcinoma) as well as mechanisms of chemoresistance to Paclitaxel have not been identified yet. Material and methods: The apoptotic effects and mechanisms of Paclitaxel on different permanent HNSCC cell lines (UT SCC 24A, UT SCC 24B, UT SCC 60A and UT SCC 60B) were determined by flow cytometry assays, Polymerase Chain Reaction (PCR) analysis, immunofluorescence based assays and sequencing studies. Results: Our data indicate a Paclitaxel induced G2/M arrest in HNSCC followed by an increased amount of apoptotic cells. Moreover, the activation of caspase 8, caspase 10 and caspase 3, and the loss of the mitochondrial outer membrane potential could be observed, whereas an activation of caspase 9 could barely be detected. The efficient activation of caspase 9 was not effected by altered methylation patterns. The Apaf 1 promoter region was not methylated in the HNSCC. Sequencing analysis revealed two isoforms of caspase 9, the pro apoptotic caspase 9 and the anti apoptotic caspase 9b, which is missing the catalytic site and acts as an endogenous inhibitor of apoptosis by blocking the binding of caspase 9 to Apaf 1 to form the apoptosome. Conclusion: Thus, our data demonstrate the presence of anti-apoptotic caspase 9-b in HNSCC, which may serve as a promising target to increase chemotherapeutic apoptosis induction.